Parental strand recognition of the DNA replication origin by the outer membrane in Escherichia coli. - Herrick, J (1994)
The outer membrane of Escherichia coli binds the origin of DNA replication (oriC) only when it is hemimethylated. We report here the results of a footprinting analysis with the outer membrane which demonstrate that its interaction with oriC occurs mainly at the left moiety of the minimal oriC, where 10 out of 11 Dam methylation sites are concentrated. Two regions, flanking the Integration Host Factor (IHF) sites, are preferentially recognized at the minimum membrane concentration at which oriC plasmid replication is inhibited in vitro. We have identified the putative proteins involved in hemimethylated oriC binding and cloned one of the corresponding genes (hobH). The purified LacZ-HobH fusion protein specifically binds oriC DNA at the same preferential sites as the membrane. A mutant of the hobH gene reveals partial asynchronous initiation of DNA replication.